Incidence of atrioventricular block after isolated coronary artery bypass grafting: a systematic review and pooled-analysis - Yaghoobian, Ramin; Hosseini Dolama, Reza; Soleimani, Hamidreza; Saeidi, Sahar; Mashayekhi, Mahtab; Mirzayi, Parsa; Alavi Tabatabaei, Ghazaal; Hosseini, Kaveh (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background and Objectives: Atrioventricular block (AVB) is a serious complication following coronary artery bypass grafting (CABG) surgery, and its high-grade form may necessitate the implantation of a permanent pacemaker (PPM). AVB is associated with increased morbidity and mortality rates. This study aims to estimate the incidence of AVB and subsequent PPM implantation after isolated CABG surgery. Material and Methods: We searched electronic databases of PubMed, Embase, and Scopus from inception to November 18, 2022. Clinical trials and observational studies reporting the incidence of post-CABG AVB or subsequent PPM implantation in adult patients were included. The total incidence for all included outcomes was calculated using the inverse variance method, and the I2 statistic was reported to evaluate the heterogeneity of studies. Results: A total of 28 studies met the inclusion criteria. Four studies (3 cohorts, 1 randomized controlled trial (RCT)) reported AVB without specifying its type; one (cohort) reported different degrees of AVB, 20 (12 cohorts, 8 RCTs) reported complete heart block (CHB) (or AVB requiring temporary pacing), and nine (8 cohorts, 1 RCT) reported the number of PPM inserted due to AVB. The pooled incidence of AVB, CHB (or AVB requiring temporary pacing), and PPM due to AVB was 1.16%, 1.73%, and 0.58%, respectively. Meta-regression analysis revealed that age, gender, diabetes, hypertension, hyperlipidemia, or smoking were not significantly associated with AVB, CHB, or PPM implantation. Conclusion: This study highlights the incidence of AVB and the need for PPM implantation following CABG surgery. The findings emphasize the importance of postoperative monitoring and surveillance to improve patient outcomes.